Flipped classroom approach of language education: a systematic review - Mazlan, Rohaida; Mahamod, Zamri; Jamaludin, Khairul Azhar (International Journal of Evaluation and Research in Education (IJERE), 2025)
The flipped classroom approach has emerged as an innovative pedagogical model in language education, transforming traditional teaching methods by reversing the conventional sequence of instruction and homework. The objectives of this systematic literature review are to examine the impact of various technological enhancements on the effectiveness and student engagement in flipped classrooms. Secondly, to explore the perceptions and attitudes of students and teachers towards flipped classroom methodologies across different educational contexts. Thirdly, to assess the effects of flipped classroom approaches on students’ academic performance and critical thinking skills across various disciplines. This study conducted an extensive search of scholarly articles from reputable databases such as Scopus and Web of Science, focusing on studies published from 2021 until 2024. The flow of the study is based on the PRISMA framework. The database search identified 35 final primary studies that were analyzed. The findings were divided into three themes: i) technological enhancements in flipped classrooms, which were found to significantly improve student engagement and learning outcomes; ii) student and teacher perceptions of flipped classrooms, which were generally positive, with many highlighting increased interaction and autonomy in learning; and iii) outcomes and effectiveness of flipped classroom approaches, showing a positive impact on students’ academic performance and critical thinking skills. In conclusion, the flipped classroom approach holds considerable promise for language education, offering a more effective and engaging alternative to traditional instruction. This review provides valuable insights for educators and policymakers seeking to adopt innovative teaching strategies in language education.